2019
DOI: 10.2147/ijn.s172391
|View full text |Cite
|
Sign up to set email alerts
|

<p>Single-dose Ag85B-ESAT-6 loaded&ndash;poly(lactic-<em>co</em>-glycolic acid) nanoparticles confer protective immunity against tuberculosis</p>

Abstract: Background Bacillus Calmette–Guérin, the attenuated strain of Mycobacterium bovis , remains the only available vaccine against tuberculosis (TB). However, its ineffectiveness in adults against pulmonary TB and varied protective efficacy (0–80%) speak to an urgent need for the development of an improved and efficient TB vaccine. In this milieu, poly(lactic- co -glycolic acid) (PLGA), is a preferential candidate, due to such properties as biocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Studies have shown that PEG strengthens the PLA nanoparticles in gastrointestinal (GI) fluid stability and promotes the transmit of nanoparticles to the lymphatic system through the GI mucosa [86]. Mice immunized by PLGA nanoparticles encapsulating the bivalent H1 antigen showed significant effects against tuberculosis, as the immunization provides longterm protection [87]. The limitations of PLGA nanoparticles can be overcome through extensive and comprehensive assessments of pharmacokinetics, biodistribution, and toxicity [27].…”
Section: Plgamentioning
confidence: 99%
“…Studies have shown that PEG strengthens the PLA nanoparticles in gastrointestinal (GI) fluid stability and promotes the transmit of nanoparticles to the lymphatic system through the GI mucosa [86]. Mice immunized by PLGA nanoparticles encapsulating the bivalent H1 antigen showed significant effects against tuberculosis, as the immunization provides longterm protection [87]. The limitations of PLGA nanoparticles can be overcome through extensive and comprehensive assessments of pharmacokinetics, biodistribution, and toxicity [27].…”
Section: Plgamentioning
confidence: 99%
“…Th2-type cytokines (IL-4, IL-6) play important roles in humoral response. [50][51][52][53] In Figure 8, CYPP-PEI/PCV-2 significantly promoted the levels of IFN-r, TNF-a (Th1-type cytokines), IL-4, and IL-6 (Th2-type cytokines), which indicated that CYPP-PEI nanoparticles could promote both Th1-type and Th2-type immune response. Although the content of Th2-type cytokines (IL-4, IL-6) in the CYPP-PEI group increased obviously compared with PCV-2, CYP/ PCV-2, BP/PCV-2, and control groups, their expression levels were significantly lower than Th1-type cytokines.…”
Section: Dovepressmentioning
confidence: 92%
“…The nanoparticle size, size distribution and zeta potentials of diluted Tβ-4 ethosome solution were measured using the Malvern Zetasizer Nano ZS system (Malvern, Westborough, UK) 15. The microstructure of Tβ-4 ethosomes was detected using a TEM (JEM 1200EX, JEOL, Tokyo, Japan) by dropping Tβ-4 ethosome solution onto special carbon-coated copper grids and dyeing with phosphotungstic acid (2%, w/w) for 10–15 s.…”
Section: Methodsmentioning
confidence: 99%